Diagnosis and treatment of acute lower gastrointestinal bleeding - (:unkn) unknown (My University, 2001)
Lower gastrointestinal (LGI) bleeding is a common clinical problem for which multiple diagnostic tests and therapeutic interventions have been developed but no optimal approach has been established. Acute LGI bleeding presents a difficult clinical challenge. Initial attention must always be directed at resuscitation. Endoscopy and angiography may offer accurate diagnosis and therapeutic interventions in most cases. Scintigraphy is useful for the detection of the bleeding site as well as for the identification of patients for further angiographic intervention in cases where the hemorrhage is ongoing. Although the least invasive effective solution to the bleeding problem is generally the best, emergency undirected surgery may be necessary in some patients. In that case, subtotal colectomy can be done with acceptable morbidity and mortality rates. If the bleeding site is identified, segmentary resection is preferred in the surgical treatment of LGI bleeding.
Keywords: Angiodysplasia; Angiography; Colectomy; Colonoscopy; Diverticulosis; Lower gastrointestinal bleeding; Scintigraphy